Potassium polyacrylate hydrogels reinforced with cellulose nanocrystals: Synthesis and functional properties - Pinzon-Moreno, Diego David [UNESP]; Villanueva-Pereira, Nadia Elizabeth; Gimenez-Sanchez, Abigail Paz; Rodrigues Agostinho, Gabriela; Da Costa Silva Gonçalves, Caroline; Pierina Uliana, Marciana; Rodrigues Cintra, Isabela Luiza [UNESP]; Leali Costa, Michelle [UNESP]; Cocchieri Botelho, Edson [UNESP] (Springer Nature, 2025)
Customized superabsorbent hydrogels are of significant interest across several fields of science and engineering due to their practical applications. A conventional classification of hydrogels is based on their composition, in which an ion is attached to the polymeric chain, with commercially available hydrogels typically containing of sodium ions. This composition opens the possibility of developing a less explored type of hydrogel based on potassium, which is strategic due to its role as an essential nutrient for both plant and animal life. This enable more beneficial integration into the environment or interaction with various organisms. These aspects contrast with sodium-based hydrogels, which, although more widely used commercially, may pose environmental and biological concerns, including potential toxicity, degradation of soil structure, and health risks such as hypertension and cardiovascular disorders. This study systematically examines the effects of cellulose nanocrystal (CNC) incorporation on the physicochemical properties of potassium polyacrylate-based polymeric hydrogels. Through controlled variation of CNC loading concentrations, we characterize the structure‐property relationships governing hydrogel performance. These polymeric materials were synthesized in an aqueous medium using a free radical technique and subsequently processed through drying, grinding, molding, lyophilization, and electrospinning, resulting in different forms of hydrogel presentations. The materials were characterized using cyclic swelling and deswelling tests, contact angle measurements, Fourier-transform infrared spectroscopy (FTIR), thermogravimetric analysis (TGA), differential scanning calorimetry (DSC), scanning electron microscopy (SEM), energy-dispersive X-ray spectroscopy (EDS), and optical microscopy. The results demonstrated that CNC content directly tuned key properties: FTIR/EDS confirmed CNC integration, swelling tests revealed adjustable absorption capacity, and SEM showed microstructure control in several presentations (films, electrospun mats, particles). These findings highlight the hydrogel’s customizable functionalities—swelling, and deswelling and contact angle—for requests where eco-compatibility and nutrient synergy are critical, advancing the design of adaptive, sustainable hydrogel systems.